Enhancing Laboratory Capacities and Pandemic Preparedness: A Critical Evaluation of Global Strategies and Approaches - Asiri, Ahmed Ibrahim A ,; Al Mutlaq, Abdullah Ali N,; Al Faqeer, Abulmajeed Abdullah Husain,; Al Ahmari, Saeed Saad M,; Al Hefthi, Alhassan Abdullah Alhassan,; Al Zahrani, Abdulrahman Ahmed, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2023)
This article critically evaluates global strategies and approaches for enhancing laboratory capacities in the context of pandemic preparedness. The recent global health crises have underscored the pivotal role of laboratory systems in detecting and responding to emerging infectious diseases. Despite technological advancements, there are stark disparities in laboratory infrastructures across different regions. This review delves into the current state of laboratory systems worldwide, highlighting key challenges such as funding, training, equipment shortages, and coordination difficulties. It also examines global strategies adopted by health organizations, emphasizing the integration of new technologies in diagnostics and research, and the crucial role of data management. Furthermore, the article explores the significance of building a collaborative global network for resource sharing and effective partnership, drawing on case studies and best practices from various countries. The findings suggest that strengthening laboratory capacities requires a multi-faceted approach, involving not only technological investments but also policy reforms and international cooperation. The review concludes with recommendations for future directions, stressing the need for continuous evaluation and adaptation in laboratory systems to enhance global pandemic preparedness.